Comparative air conditioning performance using SiO2 and Al2O3 nanolubricants operating with Hydrofluoroolefin-1234yf refrigerant - Sharif, M.Z.; Wan Azmi, Wan Hamzah; N. N, M. Zawawi; Mohd Fairusham, Ghazali (Elsevier, 2022)
Nowadays, the automotive air-conditioning system operating with Hydrofluoroolefin-1234yf or R1234yf refrigerant is used to reduce the global warming potential. This study aims to investigate the performance of SiO2 and Al2O3 nanolubricants with R1234yf refrigerant in the automotive air conditioning system. The polyalkylene glycol-based nanolubricant was prepared using a two-step preparation method, and the stability of the nanolubricant was assessed using visual sedimentation observation and zeta potential analysis. The experimental investigation on the performance of automotive air conditioning system with R1234yf was undertaken for the SiO2 and Al2O3 nanolubricants at different volume concentrations and various operating conditions. The system with SiO2 nanolubricant at 0.01% volume concentration demonstrated the best cooling capacity performance with an average enhancement of 15.7%. On the other hand, the highest coefficient of performance increment and power consumption reduction were attained up to 9.8% and 27.1%, respectively for Al2O3 nanolubricant at 0.05% volume concentration. The SiO2 nanolubricant performed with better cooling capacity, higher power consumption and lower coefficient of performance than the polyalkylene glycol-based lubricant. In contrast, the Al2O3 nanolubricant improved the coefficient of performance and reduced the power consumption. Since both nanolubricants provide their respective advantages, more research into integrating the two nanoparticles for refrigeration systems with R1234yf refrigerant is encouraged.